Status of Oxidants and Antioxidants in Acne Vulgaris: A Cross-sectional Study - Astha Goyal; Sanjiv Kumar Bansal; Shikhar Ganjoo; Busi Karunanand (Journal of Clinical and Diagnostic Research)
Introduction: Acne vulgaris is a multifactorial dermatological disease. The role of oxygen free radicals and antioxidant enzymes has been implicated in the pathophysiology of several skin diseases, including acne. However, the relationship between acne vulgaris and oxidative stress biomarkers lacks a clear consensus. Aim: To investigate the existence of oxidative stress in patients with acne vulgaris by measuring the levels of an oxidant, Malondialdehyde (MDA), and antioxidants such as Superoxide Dismutase (SOD), Catalase (CAT), and Glutathione (GSH). Materials and Methods: This cross-sectional study was carried out in the Department of Biochemistry in association with the Department of Dermatology and Venereology at the Faculty of Medicine and Health Sciences, SGT University, Budhera, Gurugram, India over a period of 12 months from July 2023 to June 2024. The study involved 200 patients with acne vulgaris and 50 healthy adults in the control group, aged 18-45 years. Five millilitres of venous blood was taken into gel separator tubes for the parameters such as SOD, CAT, GSH, and MDA, which were measured using Enzyme-linked Immunosorbent Assay (ELISA) kits. The values were compared with those of the control group. Student’s t-test was applied, and a p-value of <0.05 was considered statistically significant. Results: The mean age of the cases was 26.24±6.56 years, with 121 females and 79 males, while the healthy controls had a mean age of 25.80±5.45 years, with 29 females and 21 males. The serum levels of SOD (8.75±2.92 U/mL), CAT (0.22±0.08 ng/mL), and GSH (0.61±0.25 ng/mL) were found to be statistically decreased in patients with acne vulgaris compared to healthy controls, who had mean±SD values of 89.39±9.91 U/mL, 8.99±4.02 ng/mL, and 18.77±6.50 ng/mL, with a p-value of <0.001, respectively. Additionally, the serum MDA levels were found to be statistically increased in patients with acne vulgaris (7.72±2.11 nmol/mL) compared to healthy controls (2.51±0.97 nmol/mL), with a p-value of ≤0.001. Conclusion: The present study clearly demonstrated the existence of oxidative stress in patients with acne vulgaris, indicating its crucial role in the pathophysiology of acne alongside inflammation. Additionally, incorporating atleast one antioxidant-based medication into the combined acne treatment regimen may prove beneficial.